Analisis Penerapan MRP Terhadap Perencanaan Dan Pengendalian Persediaan Bahan Baku Pada PT. Latif Di Kediri - Gunawan Wibisono; Sri Rahayuningsih; Heribertus Santoso (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2017)
Library activities that are immediately felt by users are services, because service is the spearhead of the library. At this service the ongoing relationship between users and service providers. This study aims to categorize the attributes and weaknesses of service quality Kadiri University library based on the Kano method. This research uses quantitative survey types with analytical descriptive methods. The results of the research analysis showed that the services provided were still lacking. Categories must be of tangible variables, reliability, responsiveness that are considered weaknesses and must be improved and one-dimensional categories of assurance and empathy variables are profit and need to be improved. Furthermore, from the calculation of animal satisfaction and visitor satisfaction obtained 62% of visitor satisfaction and obtained 92% of visitor disappointment. The greatest satisfaction is obtained from the 25th attribute, namely officers who provide services neatly, politely and friendly. While the attribute with the lowest customer satisfaction value is the 17th attribute included in the must-be category, namely the suitability of available collections and available information. Indicates attributes that have little importance to customer satisfaction. Furthermore, for the disappointment visitors get the 25th attribute, which is to deny not providing services neatly, politely and friendly. And for the high level of disappointment is the 1st attribute classified as indifferent, namely the location of the strategic library layout.PT. Latif merupakan industri yang bergerak dalam bidang furniture rotan sintetis, yang salah satu produk terlaris adalah SH-15. Masalah dalam penelitian ini mengenai persediaan bahan baku dengan menggunakan sistem made in order. Oleh karena itu dibutuhkan suatu sistem informasi yang diharapkan dalam pemenuhan kebutuhan bahan baku dapat dilakukan dengan tepat dan penentuan biaya persediaannya dapat ditetapkan seoptimal mungkin yaitu melalui penerapan MRP. Variabel penelitian dalam hal ini adalah perencanaan persediaan bahan baku. MRP diawali dengan melakukan peramalan akan jumlah permintaan/ produksi untuk waktu yang akan datang. Peramalan ini dilakukan dengan menggunakan metode Moving Average N = 1, dan Single Exponential Smoothing  = 0.8. Lalu ditentukan nilai terkecil dari SEE, MAD, dan MAPE dari masing-masing metode. Setelah terpilih salah satu metode terbaik maka metode tersebut akan dijadikan landasan untuk meramalkan jumlah kebutuhan permintaan selama satu tahun kedepan. Perbandingan antara biaya persediaan minimum metode Lot for Lot sebesar Rp.60.000 dan Part periode Balancing sebesar Rp. 44.733.750,-. Dari hasil penghitungan kedua lot sizing dapat diambil kesimpulan bahwa penerapan metode Lot Sizing Lot for Lot untuk setiap bahan baku SH-15 pada PT. Latif dapat meminimalkan biaya total persediaan sebesar Rp 60.000,- apabila dibandingkan dengan metode Lot Sizing Part Period Balancing.